The seismic DMT in an unsaturated tropical soil - Giacheti, Heraldo L. [UNESP] (2017)
The Seismic Dilatometer (SDMT) test has been increasingly used for stratigraphical logging and for defining geomechanical parameters required for geotechnical design; however there are few examples of using it on site characterization of unusual geomaterials. This paper presents and discusses the use of SDMT for site characterization of typical unsaturated tropical soil profile from Brazil. The results showed that the SDMT was appropriate for detailed stratigraphic logging and estimative of geotechnical parameters. The Go/MDMT and Go/ED ratios were used to identify unusual soil behavior. The seasonal variability on SDMT data was also discussed, and it should be considered for proper site characterization of unsaturated soils.